The Activation of Protamine 1 Using Epigenome Editing Decreases the Proliferation of Tumorigenic Cells - Namous, Hadjer; Braz, Camila Urbano; Wang, Yiding; Khatib, Hasan (Frontiers in Genome Editing, 2022)
DNA methyltransferases (DNMT) and histone deacetylases (HDAC) inhibitors are used as cancer epigenome drugs. However, these epigenetic drugs lack targeting specificity and could risk inducing genome instability and the expression of oncogenes. Therefore, there is a need to develop new therapeutic strategies where specific cancer genes can be targeted for silencing or activation. The CRISPR-dCas9 system represents a promising, powerful therapeutic tool because of its simplicity and specificity. Protamine 1 (PRM1) is exclusively expressed in sperm and has a vital role in the tight packaging of DNA, thus inducing transcriptional silencing in sperm cells. We hypothesized that the activation of the PRM1 gene in tumorigenic cells would lead to DNA condensation and reduce the proliferation of these cells. To test our hypothesis, we transfected human embryonic kidney cells 293T with a dCas9-P300 plasmid that adds acetyl groups to the promoter region of PRM1 via specific gRNAs plasmids. RNA-Seq analysis of transfected cells revealed high specificity of targeted gene activation. PRM1 expression resulted in a significant decrease in cell proliferation as measured by the BrdU ELISA assay. To confirm that the activation of PRM1 was due to acetyl groups deposited to H3K27, a ChIP-qPCR was performed. The acetylation of the PRM1 promoter region targetted by dCas9-p300 in transfected cells was higher than that of the control cells. Interestingly, the targeted promoter region for acetylation showed reduced DNA methylation. These findings demonstrate the efficacy of epigenome editing in activating PRM1 in non-expressing tumorigenic cells, which could be used as a promising therapeutic strategy in cancer treatment.